Trading numbers vs. rights? Accounting for liberal and restrictive dynamics in the evolution of asylum and refugee policies. Issue 4 (15th March 2016) - Thielemann, Eiko; Hobolth, Mogens
ABSTRACT: The recent evolution of asylum and refugee policies in developed countries has been characterised by two apparently contradictory dynamics. Efforts to limit the number of asylum applicants have coincided with the strengthening of rights for asylum seekers and refugees inside existing protection systems. The 'numbers vs. rights' model seeks to explain such counter-veiling trends as a trade-off, as the result of attempts to manage costs within given budget constraints. The model suggests that high numbers of migrants will tend to go hand in hand with attempts to restrict their rights, while low numbers will typically be associated with more rights. This paper provides a critical analysis of the model when applied to asylum and refugee policies and examines its explanatory purchase through the analysis of longitudinal data on visa and asylum statistics. We argue that while the model provides an interesting framework through which to analyse executive decisions in this field, it underestimates the opportunities and constraints provided by the institutional context in which policy choices are made. We argue that 'over-time' variation in the influence of non-majoritarian institutions (in Europe, increasingly those operating at the EU level) provide a more compelling account of the dynamics of asylum and refugee policies over time than the political economy predictions of a 'number vs. rights' trade-off.